PENGARUH PENERAPAN KURIKULUM MERDEKA TERHADAP PEMBENTUKAN KARAKTER SISWA - Walib Abdullah; Sayyidatul Munawwaroh (STIT Al-Ibrohimy Bangkalan, 2023)
THE INFLUENCE OF IMPLEMENTING AN INDEPENDENT CURRICULUM ON STUDENT CHARACTER FORMATION, The focus of this study is on two issues. The first is whether the autonomous curriculum's implementation has had any impact on the development of the students' character at SMP Negeri 3 Pamekasan. Second, how much of an impact does the Independent Curriculum's implementation have on SMP Negeri 3 Pamekasan students' development of character? The participants in this study were 158 kids in class VII at SMP Negeri 3 Pamekasan; because this number was higher than 100, the researchers included 40 students, or 25% of the entire population. Questionnaires and written records are the instruments utilized in data collecting. Between January 26 and February 27, 2023, data were collected. Product Moment statistical analysis was the method employed for data analysis. First, the implementation of the independent curriculum at SMP Negeri 3 Pamekasan had an impact on how students formed their character. This was clear from the data analysis results, which showed that the r count value was 0.723 higher than the product moment r table value, where at N=40 in a 5% confidence interval, a value of 0.312 and a value of 0.403 were achieved. Second, because the rcount value of 0.723 is in a range of numbers from 0.600 to 0.800 with a high/strong correlation, the application of the independent curriculum at Pamekasan 3 Public Middle School has a pretty significant impact on the development of student character. Keywords: Independent Curriculum , Student Character